1976
DOI: 10.1007/bf00224303
|View full text |Cite
|
Sign up to set email alerts
|

Cell differentiation of the fetal rat anterior pituitary in vitro

Abstract: Adenohypophysial primordia of rat embryos at 13 to 15 days gestation were cultured in Parker 199 synthetic medium for 2 to 11 days. At the end of the culture period their fine structure and the presence of immunoreactive trophic hormones using the peroxidase-labeled antibody technique were investigated. The degree of differentiation in the glands depends largely on the age of the embryos furnishing the explants. Cultured pituitaries explanted on the 13th day of gestation contain only ACTH-positive cells and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

1978
1978
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 11 publications
2
20
1
Order By: Relevance
“…At E9.5-10 in mice the anterior wall of Rathke's pouch is in direct apposition with the floor of the diencephalon (Schwind 1927;Rugh 1968;Kaufman 1992). There has been a debate focused on the possibility that the floor of the dienceph o alon may be "induced" to form the neurohypophysis by the presence of the Rathke's pouch, or vice versa (Nemesk6ry et al 1976;Daikoku et al 1982Daikoku et al , 1983Watanabe 1982a, b). In normal E11-13 mouse embryos (this study) and rat embryos (Lazzaro et al 1991 Our results showed further that despite the lack of normal hypothalamus and pituitary, the T/ebp null homozygous mice developed full term in their mother's womb with only a slight decrease in body weight at birth.…”
Section: In Situ Hybridization Results Showed That the T/ebpmentioning
confidence: 99%
“…At E9.5-10 in mice the anterior wall of Rathke's pouch is in direct apposition with the floor of the diencephalon (Schwind 1927;Rugh 1968;Kaufman 1992). There has been a debate focused on the possibility that the floor of the dienceph o alon may be "induced" to form the neurohypophysis by the presence of the Rathke's pouch, or vice versa (Nemesk6ry et al 1976;Daikoku et al 1982Daikoku et al , 1983Watanabe 1982a, b). In normal E11-13 mouse embryos (this study) and rat embryos (Lazzaro et al 1991 Our results showed further that despite the lack of normal hypothalamus and pituitary, the T/ebp null homozygous mice developed full term in their mother's womb with only a slight decrease in body weight at birth.…”
Section: In Situ Hybridization Results Showed That the T/ebpmentioning
confidence: 99%
“…Moreover, the work of Meusy-Dessolle (1974) Nemeskery et al, 1976 ;Watanabe and Daikoku, 1976 ;Begeot et al, 1979 ;birds : Ferrand et al, 1980). The same results were obtained after early encephalectomy in utero in rat (Chatelain et al, 1976, 19791.…”
mentioning
confidence: 99%
“…The available results of in vitro experi ments are variable and unsatisfactory because of the use of uncontrolled serum in the culture medium [5,14,30] or the use of synthetic medium deprived of hormones and growth factors [22]. However, in a previous report we showed that insulin and transferrin added to the culture medium could stimulate the spontaneous differentiation of gonadotrophs in adenohypophysial primordia maintained in organ culture [4], However, we showed that other stimulating factors were also involved since these cells were not able to differentiate Received: April 22, 1983 Accepted after revision: August 19, 1983 in these conditions of culture, when the explantation was performed at a very early stage.…”
mentioning
confidence: 99%